Journeying Filipinas: Classification of Travel Writings by Filipino Women Travelers - Chloe Intruso Cadiz (Journal of Language and Literature, 2024)
Travel writings’ long literary tradition in the West had often been viewed as a colonial discourse and had prepared a colony of readership, particularly the narratives during the 19th century (Spurr,1993). However, travel writing is relatively new in the Philippines, and a lot of Filipino women are experimenting with writing in the genre. As such, this study examined the types of contemporary travel writings written by Filipino women using Fussell’s categorization (1982) for travel writings according to the writer's intent of travel: explorer, tourist, and travel. Some of the selected texts fit the said categories, while others combined the mentioned classifications. In this study, the explorer category was also expanded to cover traveler's subjective experiences to accommodate some texts that exemplify this type of narrative. Moreover, the study utilized grounded theorizing (Glaser Strauss, 1967; Strauss Corbin, 1990) to classify other travel texts that did not fall into Fussell’s typologies, which resulted in four new categories, namely 1) backpacker; 2) escape/convalescent; 3) pilgrim; and 4) labor worker. The intent of travel adheres to global categorizations but, at the same time, reflects the fast-changing contemporary narratives accommodated into the travel writing genre which attest to how they write down their impressions and introspections on their travel experiences.